Tarnow Scientific Colloquia: Introductory remarks - Nawrocki, Michał (Health Promotion & Physical Activity, 2016)
The first, concretizing remark: Tarnowskie Colloquia Naukowe - Tarnow Scientific Colloquia is a peer-reviewed journal of the State Higher Vocational School in Tarnów, the columns of which are open to both PWSZ employees and external authors. The formula of the journal is university-wide, and takes its specific projects in the form of individual thematic issues respecting the research and methodological specificity of individual disciplines. This volume of works on health and physical culture initiates the TCN publishing cycle.